107 INTRAUTERINE GROWTH RESTRICTION DECREASES INSULIN-LIKE GROWTH FACTOR 1 MESSENGER RIBONUCLEIC ACID AND PROTEIN LEVELS IN MALE, BUT NOT FEMALE, DAY 0 RAT LUNGS. (1st January 2006) - Langen, R. L.; Humphrey, C.; Callaway, C. W.; McKnight, R. A.; Yu, X.; Lane, R. H.
Abstract : Background: Intrauterine growth restriction (IUGR) predisposes neonates towards chronic lung disease. IUGR rats suffer pulmonary hypoplasia. IGF-1 is expressed throughout lung development, and transgenic mice that lack IGF-1 suffer disproportionate decreases in lung growth. However, the effect of IUGR on IGF-1 levels in the lung has not been previously characterized. Objective: We hypothesized that IUGR would decrease IGF-1 levels in the lung. To test this hypothesis, we compared IGF-1 mRNA and protein levels in day 0 rat lungs to those of controls. Design/Methods: We used a well-characterized model of IUGR in the rat. Lungs were collected from male and female IUGR day 0 rat pups ( n = 4), as well as from male and female control day 0 rat pups ( n = 4). We isolated mRNA from these specimens and used real-time PCR to quantitate relative levels of IGF-1 mRNA as normalized to GAPDH mRNA. Subsequently, total protein extracts were quantified from samples. Western blot analysis determined relative protein levels of IGF-1 as normalized to GAPDH. Results: Data are presented as % control ± SEM. IUGR decreased IGF-1 mRNA levels when comparing male IUGR rats versus male controls (87.2% ± 1.9%, p = .011). However, female rat pups failed to exhibit this same difference in mRNA levels (107.7% ± 11.4%, p = .27). Similarly, IUGR significantly reduced IGF-1 protein levels in male IUGR rat lungs as compared to male controls (75.7% ± 9%, p = .037). Female rat pups once again did not exhibit a similar difference (103.6% ± 19.3%, p = .57%). Conclusion: We conclude that IUGR decreases IGF-1 mRNA and protein levels in male rat pup lungs as compared to controls. These same differences are not noted in female rats. We speculate that these discrepancies may be related to differences in morbidities between male and female infants.